The Contribution of Linguistics Courses to English as a Foreign Language (EFL) Learners Language Proficiency: A Case Study of Advanced EFL Student-Teachers at the Higher Teacher Education College of Porto-Novo, (École Normale Supérieure) République du Bén - LOKO, Djima Crépin (My University, 2020)
This paper is a linguistics-oriented study which explores the possible contribution linguistics and phonetics courses can offer EFL student-teachers in preparing them for their communicative fluency. In actual fact, after seven years of study in secondary school (with English taught as subject), students who successfully pass their A- levels can register in the English section. Thus, one can take for granted that the student-teachers have the linguistic background to be fluent speakers of English. Unfortunately, it is noted that some of them lack fluency not only during formal conversation but also during informal one. The present study is sustained by a qualitative and quantitative method of investigation to pinpoint responsibilities and causes of this situation. Such research instruments as questionnaires and interviews have been used to get information from students. The results reveal the difficulties encountered by the student- teachers are of three types viz. (i) the students‟ lack of involvement and commitment in the course aims and objectives, (ii) their lack of immersion in the target language via active participations in English clubs and language trips to English speaking countries, and (iii) their lack of didactic material (at the personal level), which hinders the good will of some. Above all, the study concludes that the poor level of the selected student-teachers in speaking is due to the lack of personal practice with their teachers and peers who happen to be very fluent though they all have been trained in the same setting and context.
Keywords: Linguistics; Language Proficiency; Meaning construction; Student-; teachers; Speaking.